2010
DOI: 10.1371/journal.pgen.1001188
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Effects of Long-Term Divergent Selection

Abstract: To understand the genetic mechanisms leading to phenotypic differentiation, it is important to identify genomic regions under selection. We scanned the genome of two chicken lines from a single trait selection experiment, where 50 generations of selection have resulted in a 9-fold difference in body weight. Analyses of nearly 60,000 SNP markers showed that the effects of selection on the genome are dramatic. The lines were fixed for alternative alleles in more than 50 regions as a result of selection. Another … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
179
0
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 137 publications
(195 citation statements)
references
References 29 publications
15
179
0
1
Order By: Relevance
“…Evolution would seem likely to start with this variation, as long as it is relevant to selection and not unduly constrained by correlations with other traits. Fitting this expectation, the immediate and dramatic evolutionary responses often seen in artificial selection experiments suggest that plenty of relevant variation is present (Moose et al, 2004;Hill and Kirkpatrick, 2010;Johansson et al, 2010;Lango Allen et al, 2010). Although the results of these studies might seem of questionable relevance because the selection was not 'natural,' similarly rapid responses have been observed in natural populations experiencing environmental change (Hendry and Kinnison, 1999;Reznick and Ghalambor, 2001;Hendry et al, 2008).…”
Section: Ecosystem Functionmentioning
confidence: 83%
See 2 more Smart Citations
“…Evolution would seem likely to start with this variation, as long as it is relevant to selection and not unduly constrained by correlations with other traits. Fitting this expectation, the immediate and dramatic evolutionary responses often seen in artificial selection experiments suggest that plenty of relevant variation is present (Moose et al, 2004;Hill and Kirkpatrick, 2010;Johansson et al, 2010;Lango Allen et al, 2010). Although the results of these studies might seem of questionable relevance because the selection was not 'natural,' similarly rapid responses have been observed in natural populations experiencing environmental change (Hendry and Kinnison, 1999;Reznick and Ghalambor, 2001;Hendry et al, 2008).…”
Section: Ecosystem Functionmentioning
confidence: 83%
“…A scarcity of genes of large effect also appears to be the case for many other human traits, including susceptibility to diseases (Manolio et al, 2009). In addition, artificial selection studies clearly show that evolutionary changes are often driven by many genes (Hill and Kirkpatrick, 2010), with classic examples including oil and protein content in maize (Zea mays) (Moose et al, 2004) and body weight in chickens (Gallus gallus domesticus) (Johansson et al, 2010).…”
Section: Ecosystem Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subjecting populations to artificial selection provides an accelerated evolutionary process that may result in extreme phenotypes with accompanying changes across the genome [2][3][4]. Using such experiments, the contribution by mutational variance to the evolution of quantitative traits can be quantified by, for example, measuring the release of genetic variance during selection experiments from an inbred founder population [5].…”
Section: Introductionmentioning
confidence: 99%
“…Based on work on complex traits in other species, we might expect many more loci with effects too small to be detected in our current sample to influence a complex behavioral trait like tameness (e.g., Yang et al 2010;Hunt et al 2013). Further, selection experiments in multiple species (Drosophila (Burke et al 2010), maize (Laurie et al 2004), and chickens (Johansson et al 2010;Pettersson et al 2013) demonstrated that many loci typically respond to strong selection, as expected when trait variation is due to variants at many genes. It thus seems plausible that many genetic variants with small effects contribute to differences in several biological pathways that together shape complex behavioral traits such as tameness and defensive aggression.…”
Section: Discussionmentioning
confidence: 81%